What forage tree-shrub species are recommended in alley cropping systems under west Asia conditions? - Louhaichi, Mounir; Hassan, Sawsan (Université Laval, 2023)
Alley cropping is an agroforestry practice of planting arable crops between trees or shrubs. The integration of forage treeshrub species in an alley-cropping system was examined as an approach to mitigate the effects of climate-induced drought, to improve soil quality and to secure better livelihoods for smallholder famers in West Asia. Forage tree-shrub performance was evaluated in an alley-cropped system using seven leguminous forage species (Medicago arborea, Colutea istria and Coronilla glauca), three Atriplex species (A. canescens, A. nummularia, A. undulata) and spineless cactus pear (Opuntia ficus indica) intercropped between annual crops of wheat, vetch and barley at the Mushaqqar Research Station in Jordan. Growth characteristics were measured by monitoring tree-shrub stem diameter, stomatal conductance, plant height and estimating tree-shrub biomass production. The suitability index was based on growth characteristics for each tree-shrub. Results showed that the Atriplex species showed a higher suitability index compared to leguminous shrubs and cactus pear. Among the Atriplex species, Atriplex canescens recorded the highest plant height, stem diameter and estimated biomass production across all three field crops. Leguminous species recorded low biomass productivity at the beginning of summer but with a low suitability index. Despite their vital role in soil nutrient improvement, there were found to be unreliable in providing supplement forage for livestock. The cactus pear recorded a low suitability index and is not recommended. When implementing alley cropping systems, a balance should be considered between high forage biomass shrub species accessible to livestock after harvesting crops and shrubs that enhance soil nutrient status for improving field crop growing conditions.